The role of NagC in Yersinia pestis and Yersinia pseudotuberculosis biofilm development and insect transmission - Elton, Linzy (2019)
There are three species of human-pathogenic Yersiniae; two of which cause gastrointestinal disease (Yersinia pseudotuberculosis and Yersinia enterocolitica) and one which causes plague (Yersinia pestis), one of the deadliest diseases in human history. Whilst Y. pseudotuberculosis and Y. enterocolitica are transmitted faeco-orally, Y. pestis is transmitted by insects, classically the Oriental rat flea, Xenopsylla cheopis. All Yersiniae are capable of a method of bacterial messaging known as quorum sensing (QS), which allows individual cells to communicate in a density dependent manner using signalling molecules such as N-acyl-homoserine lactones (AHLs). QS regulates several virulence phenotypes, including the production of Yersinia virulence factors (YOPs), secreted by the type three secretion system (T3SS) into mammalian host cells, auto-aggregation and biofilm formation.